1998
DOI: 10.1046/j.1365-2249.1998.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement regulation in innate immunity and the acute-phase response: inhibition of mannan-binding lectin-initiated complement cytolysis by C-reactive protein (CRP)

Abstract: Mannan-binding lectin (MBL) is an acute-phase protein which activates complement at the level of C4 and C2. We recently reported that the alternative pathway also is required for haemolysis via this 'lectin pathway' in human serum. CRP is another acute-phase reactant which activates the classical pathway, but CRP also inhibits the alternative pathway on surfaces to which it binds. Since serum levels of both proteins generally increase with inflammation and tissue necrosis, it was of interest to determine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…In this context it is worth noting that we have previously shown an association of AER with the inflammatory markers CRP and IL-6 in diabetic patients with incipient or overt nephropathy [3]. One explanation for the lack of correlation between MBL and inflammatory markers could also come from the simple fact that CRP may inhibit the production of MBL [14,15]. On the other hand, it has been suggested that MBL and CRP are [15].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this context it is worth noting that we have previously shown an association of AER with the inflammatory markers CRP and IL-6 in diabetic patients with incipient or overt nephropathy [3]. One explanation for the lack of correlation between MBL and inflammatory markers could also come from the simple fact that CRP may inhibit the production of MBL [14,15]. On the other hand, it has been suggested that MBL and CRP are [15].…”
Section: Discussionmentioning
confidence: 91%
“…One explanation for the lack of correlation between MBL and inflammatory markers could also come from the simple fact that CRP may inhibit the production of MBL [14,15]. On the other hand, it has been suggested that MBL and CRP are [15]. Even if we could not confirm a relationship between MBL and eGDR in the multivariate analysis, there was a negative correlation between MBL and eGDR as well as between MBL and HDL cholesterol in the simple regression analysis, suggesting that MBL may be a marker of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…When patients were divided according to the median level of MBL measured close to diabetes onset and before the development of microalbuminuria, there was a significantly higher cumulative incidence of persistent micro-or macroalbuminuria in patients with serum MBL above the median than in those patients with levels below the median (41% [CI 31-50] vs. 26% [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]; P ϭ 0.003). Furthermore, we have demonstrated for the first time that a high level of MBL early in the course of type 1 diabetes is significantly associated with later development of persistent micro-or macroalbuminuria, suggesting that MBL-initiated complement activation may be involved in the pathogenesis of microvascular complications in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adjustments for differences in CRP levels have had no impact on the association between MBL and microvascular complications (5). Even though CRP and MBL are closely interrelated in inflammation and CRP may inhibit MBL activity (26), the evaluation of these markers of inflammation gives rise to different information in the diabetic patients. The association of blood pressure, endothelial damage, and serum MBL remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…17 Surface-bound CRP decreases the alternative complement pathway C3-convertase and C5-convertase activities, inhibits the alternative amplification loop and reduces deposition of C3b and lysis by the lectin pathway. [18][19][20] An important observation to understand the complex biological role of CRP-induced complement activation was the description of a direct binding of the complement regulatory proteins factor H (FH) 21 and C4b-binding protein (C4BP) 15 to CRP. These inhibitory effects result from an increased binding of complement regulatory protein FH to CRP-coated surfaces.…”
Section: Introductionmentioning
confidence: 99%